The impact of governance tensions on disaffiliation from interorganizational networks - Gabriel Azeredo; Ana Luiza de Araújo Burcharth; Douglas Wegner (Administrative Sciences, 2024)
Collaboration in interorganizational networks requires specific governance choices to align participants with collective goals. However, these choices often fail to mitigate conflicts and may catalyze tensions that lead to disaffiliation. This study investigates four critical tensions identified in existing literature: (1) efficiency versus inclusion in decision-making; (2) flexibility versus stability; (3) internal versus external legitimacy; and (4) unity versus diversity. Through a case study of a credit union that disaffiliated from a cooperative network, we explore how these tensions manifest and their repercussions on both the network's functionality and the behavior of its members. Our findings reveal that such governance tensions can be harmful both to the network and to the participating organizations. Tensions between unity and diversity, stability and flexibility, and external and internal legitimacy can compromise the effectiveness of the network and even hinder participating organizations in conducting their business. In extreme situations, these tensions contribute to the strategic decision to disaffiliate. This research extends theoretical understanding by delineating the specific impact of governance tensions on exit decisions within interorganizational networks.
Keywords: 350; interorganizational networks; network governance; tensions; disaffiliation from participation; case study